Coefficient of normal restitution of viscous particles and cooling rate of granular gases - Schwager, Thomas; Pöschel, Thorsten (Physical Review E, 1998)
We investigate the cooling rate of a gas of inelastically interacting particles. When we assume velocity-dependent coefficients of restitution the material cools down slower than with constant restitution. This behavior might have a large influence to clustering and structure formation processes.